Olaparib Combined With Dacomitinib in Osimertinib-Resistant Brain and Leptomeningeal Metastases From Non-Small Cell Lung Cancer: A Case Report and Systematic Review - Zhang, Hui; Wang, Yong; Wu, Huaguo; Zhou, Shizhen; Li, Shuo; Meng, Xiangji; Tao, Rongjie; Yu, Jinming (Frontiers in Oncology, 2022)
Lung cancer patients with brain and leptomeningeal metastases usually have poor prognosis. For those patients with EGFR mutations, osimertinib, a third-generation tyrosine kinase inhibitor (TKI), is the first choice of treatment. However, drug resistance to osimertinib frequently occurs; and to date, the available follow-up treatment strategies have limited efficacy. In this case study, we report that treatments with olaparib, a Poly (ADP-ribose) polymerase (PARP) inhibitor, combined with dacomitinib, a second-generation EGFR TKI, benefited a lung cancer patient with osimertinib-resistant brain and leptomeningeal metastases. This 55-year-old male patient was found to have a pL858R mutation on EGFR exon 21 combined with TP53 and ERBB2 mutations after developing drug resistance to osimertinib treatment. Based on the genetic testing results, he was treated with olaparib and dacomitinib, and obtained 6 months of progression-free survival (PFS) and 13 months of overall survival (OS) after the diagnosis of leptomeningeal metastasis. This case report represents the first study applying PARP inhibitor in combination with dacomitinib in the treatment of leptomeningeal metastases after osimertinib resistance.